Evaluation of graphite size of modified ductile ni-resist with higher manganese - Khairul Ihsan, Yaakob; Mohd Rashidi, Maarof; Muhammad Aminuddin, Rosnizan; Mohamed Reza Zalani, Mohamed Suffian; Asnul Hadi, Ahmad (Penerbit Akademia Baru, 2024)
These days, batteries, applications requiring high temperatures, and corrosive environments are the main uses for nickel. The rise in electric and hybrid vehicles has increased the amount of nickel used as the primary component in alloys. Because of this, the price of nickel had peaked and was now fluctuating to attract manufacturers. One compound that is impacted is the Ni-Resist alloy. In this work, the nickel weight percentage of an alloy known as ductile Ni-resist alloy was reduced in order to reduce processing costs. The modification was looked into in an effort to minimize the cost of the alloying process by using less nickel in the alloying composition. The modification was looked into in an effort to minimize the cost of the alloying process by using less nickel in the alloying composition. During the melting stage, 10 weight percent nickel was added along with up to 12 weight percent chromium and manganese. Next, the impact of the alloying elements was investigated with respect to its mechanical characteristics and microstructure behavior. Then the graphite formation after alloy solidification was characterize to evaluate its dimension size.